The unbearable lightness of différance: The ethos of deconstruction - Meylahn, Johann-Albrecht (Verbum et ecclesia, 2016)
The unbearable lightness of différance is in reference to Milan Kundera's famous book, The unbearable lightness of being. Being is unbearably light, if interpreted as Heidegger did as either the meaning of Being or the truth of Being, yet in Derrida's response to Heidegger he argues that différance is older' than the meaning of Being, even older than the truth of Being, and thus one could argue that différance is even lighter than Being and thus even more unbearable. What possibilities does such an unbearable lightness of différance offer to human being-with (Mitsein) in a global village faced with so many socio-economic and environmental challenges? The unbearable lightness could be absolute relativism and particularism as Rawls has interpreted it or it could be the unbearable lightness of auto-deconstruction. The unbearable lightness of différance opens a socio-political space with an ethos of deconstruction and thereby response or ibility towards the other. This lightness of différance can be interpreted as a difficult liberty (difficult liberty as Levinas interprets it) or even an unbearable liberty of infinite broken chains of signifiers and yet a freedom that is held to account (that responds) to the other. This liberty is an infinite responsibility towards the other and therefore infinite responsibility towards justice (diké). Différance is liberty as all there is, is text, but this liberty is not licentiousness of absolute disconnection, but the difficult liberty of being only responsible towards the other. The question this article will grapple with is: what ethical implications can be gathered from this state of being-with, this unbearable lightness of différance in the global village?Intradisciplinary and/or interdisciplinary implications: Philosophy and philosophy of religion. The article focusses on the conversation between Heidegger and Derrida, with regards to différance and Austrag.